2004
DOI: 10.1021/la049821y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of an Endoglucanase from the HyperthermophilicPyrococcusfuriosuson Hydrophobic (Polystyrene) and Hydrophilic (Silica) Surfaces Increases Protein Heat Stability

Abstract: The interaction of an endoglucanase from the hyperthermophilic microorganism Pyrococcus furiosus with two types of surfaces, that is, hydrophobic polystyrene and hydrophilic silica, was investigated, and the adsorption isotherms were determined. The adsorbed hyperthermostable enzyme did not undergo loss of biological activity. A model was proposed for the mechanism of interaction of the enzyme with the surface based on the shape of the adsorption isotherm, the morphological characteristics of the enzyme, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Also, the same mass of enzyme was used in the solution and immobilized enzyme reactions, but this does not mean that same amount of enzyme is available to participate in the catalysis. Enzyme immobilization results in a random orientation of the physisorbed enzyme on the silica substrate, and this leads to some inactive enzyme due to buried or inaccessible active sites (Koutsopoulos et al, 2004). There may also be steric constraints on the enzyme's active site by neighboring enzyme, but this should be limited in this data by the use of $0.5 monolayer of protein, as described above.…”
Section: Mechanism Of Improved Glucose Yield For Immobilized Cellulasementioning
confidence: 99%
See 1 more Smart Citation
“…Also, the same mass of enzyme was used in the solution and immobilized enzyme reactions, but this does not mean that same amount of enzyme is available to participate in the catalysis. Enzyme immobilization results in a random orientation of the physisorbed enzyme on the silica substrate, and this leads to some inactive enzyme due to buried or inaccessible active sites (Koutsopoulos et al, 2004). There may also be steric constraints on the enzyme's active site by neighboring enzyme, but this should be limited in this data by the use of $0.5 monolayer of protein, as described above.…”
Section: Mechanism Of Improved Glucose Yield For Immobilized Cellulasementioning
confidence: 99%
“…Immobilization of an endoglucanase from the hyperthermophilic Pyrococcus furiosus was found to stabilize the enzyme against denaturation with increasing reaction temperature (Koutsopoulos et al, 2004). Gole et al (2001) reported increased enzymatic stability against shifts in pH and temperature for an immobilized fungal endoglucanase.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Thermodynamically, the extent of enzyme immobilization (adsorption) is determined by the Gibbs energy of adsorption, which, at a certain temperature, depends on the enthalpy and the entropy of adsorption. [28,29] Enthalpic driving forces include attractive or repulsive Coulombic forces and attractive van der Waals interactions between biomolecules and the interface. Entropic contributions to the Gibbs energy of adsorption may result from hydrophobic dehydration and conformational changes in the enzyme molecules.…”
Section: The Amount Of God Immobilizationmentioning
confidence: 99%
“…Previous studies have indicated that, irrespective of conformational stability arguments, proteins in aqueous solutions have the propensity to adsorb on hydrophobic surfaces. [14,28] Enzymatic Activity Tests…”
Section: The Amount Of God Immobilizationmentioning
confidence: 99%
“…[14] Therefore, immobilization research has largely focused on matrix selection and on optimizing immobilization conditions. [15][16][17][18] For example, work has addressed support surface hydrophobicity/hydrophobocity [19,20,21] and 3 enzyme solution pH. [17,22,23] These parameters have large influence on the total amount of enzyme loading and enzyme-catalyst activity.…”
Section: Introductionmentioning
confidence: 99%